Empirical Determination of the Causal Link between Private Sector Credit and Manufacturing Output in Nigeria - CHINANUIFE, Emmanuel; MADUEME, Stella. I.; ORJI, Anthony; ANTHONY-ORJI, Onyinye I. (Journal of Advanced Research in Management, 2019)
The Nigerian economy has been skewed towards a mono-economy with much reliance on the oil sector. However, with the fall in global oil price, there is now a shift of interest to a more promising sector capable of liberating the economy. This study is centered on determining the direction of causality between private sector credit and manufacturing output in Nigeria. The study utilized quarterly time series data from 1981 to 2015. The study adopted Toda and Yamamoto approach to granger causality in determining the existence of long run association between private sector access to credit and manufacturing output. The result of the Toda Yamamoto Granger causality test showed that there exists a bi-directional causality between private sector access to credit and manufacturing output in Nigeria. The study however recommends that in order to boost the manufacturing productivity in Nigeria, credit should be made available to the private sector at lower cost and effort should be made by government to establish a monitoring framework that will guide the activities of the manufacturing sector to ensure effective utilization of the available credit.